2016
DOI: 10.1152/advan.00071.2015
|View full text |Cite
|
Sign up to set email alerts
|

Doing peer review and receiving feedback: impact on scientific literacy and writing skills

Abstract: Doing peer review has been effectively implemented to help students develop critical reading and writing skills; however, its application in Human Physiology programs is limited. The purpose of the present study was to determine the impact of peer review on Human Physiology majors' perceptions of their scientific literacy and writing skills. Students enrolled in the Scientific Writing course completed multiple writing assignments, including three revisions after receiving peer and instructor feedback. Students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 49 publications
(112 reference statements)
0
10
0
1
Order By: Relevance
“…The research abstract project, the final element of the course, was intended to accomplish a number of goals: to teach students about scientific writing and communication principles, to develop these critical competencies in them as a different form of writing than the reflective assignments had involved, and to introduce them to the peer review process. Such structured grant-writing and peer-review exercises can develop these skills, and support real-world applications of research questions to problems (the focus of design-thinking), and promote critical analyses of literature, which had been encouraged throughout the Maymester [ [67] , [68] , [69] , [70] ]. In some cases in prior research, the peer-review instructional process was not as accelerated as in this course, but the principles and intended outcomes were similar.…”
Section: Teaching Methodsmentioning
confidence: 99%
“…The research abstract project, the final element of the course, was intended to accomplish a number of goals: to teach students about scientific writing and communication principles, to develop these critical competencies in them as a different form of writing than the reflective assignments had involved, and to introduce them to the peer review process. Such structured grant-writing and peer-review exercises can develop these skills, and support real-world applications of research questions to problems (the focus of design-thinking), and promote critical analyses of literature, which had been encouraged throughout the Maymester [ [67] , [68] , [69] , [70] ]. In some cases in prior research, the peer-review instructional process was not as accelerated as in this course, but the principles and intended outcomes were similar.…”
Section: Teaching Methodsmentioning
confidence: 99%
“…Peer review is a very demanding task. 1 While educational resources to perform effective peer reviewing are provided by several journals, 4 10 11 mentorship could contribute to the development of reviewing skills by trainees, similar to the other aspects of academic work. 12 13 The innovative programme herein described, enabling systematic training of reviewing skills by engaging mentees in a ‘real world’ peer review experience, represents a win-win scenario for all parties involved.…”
Section: Strengths Of the Programmementioning
confidence: 99%
“…Peer review is the process by which research findings are evaluated for quality, significance and originality, 1 and it is the basis of the scholarly publishing system and the maintenance of high standards in research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the technology works (Chong, Goff and Dej 2012) -and particularly if the students are trained to peer review (MacArthur 2016; Landry, Jacobs and Newton 2015; Liou and Peng 2009) -CME peer review is a valuable pedagogical tool. Geithner and Pollastro (2016) have demonstrated that engaging in peer reviews not only increases writing skills but also improves scientific literacy. However, peer reviews are still underused and understudied in higher education (Dysthe and Lillejord 2012;Nicol, Thomson and Breslin 2014), despite the convincing bulk of research on the positive aspects of CME peer reviews as an educational tool.…”
Section: Introductionmentioning
confidence: 99%